Use of fans and their effects on the turf microenvironment and disease development. Issue 1 (3rd March 2022) - Peacock, Charles H.; Lyford, Paul R.
Abstract: Common turf management practices such as close mowing, high fertilization rates, and frequent watering, in combination with stressful environmental conditions, can cause creeping bentgrass ( Agrostis stolonifera L.) golf greens to decline during the summer months in warm humid climates. Conditions that prevent the natural movement of air across a putting surface can contribute to severe disease problems. Electric fans are being used to provide increased airflow across putting greens on many golf courses. The objectives of this study were to determine if fans could reduce brown patch ( Rhizoctonia solani ) disease incidence by altering the microenvironment at the canopy surface and reduce canopy temperature and leaf wetness duration and improve turf quality. The study was conducted on a mature stand of creeping bentgrass surrounded by heavy vegetation that impeded the natural movement of air across the putting surface. Fans were used to supplement ambient wind with up to 2.7 m s −1 air velocity across the experiential plots. Three 372‐W, 35.5‐cm diameter nonoscillating fans were used and operated continuously throughout the study. As wind velocity increased, turf canopy temperatures decreased. Average canopy temperatures were 28 °C at 2.7 m s −1 and 32 °C at 0.3 m s −1 . Duration of leaf wetness also decreased as wind speed increased. Average disease incidence ranged from 11 to 33% at the lowest velocities, and 0 to 7% in plots with the highest wind velocities. Results indicate that using fans on creeping bentgrass golf greens significantly affected the microclimate and disease severity was reduced with higher wind velocities. Core Ideas: Mechanically induced wind movement can improve turf quality. Mechanically induced wind movement can mitigate disease development by reducing the duration of leaf wetness. There is a minimum wind speed to be effective at improving turf quality and mitigating disease development.